2015
DOI: 10.1007/jhep07(2015)019
|View full text |Cite
|
Sign up to set email alerts
|

Integrable λ-deformations: squashing coset CFTs and AdS5 × S5

Abstract: We examine integrable λ-deformations of SO(n + 1)/SO(n) coset CFTs and their analytic continuations. We provide an interpretation of the deformation as a squashing of the corresponding coset σ-model's target space. We realise the λ-deformation for n = 5 case as a solution to supergravity supported by non-vanishing five-form and dilaton. This interpolates between the coset CFT SO(4, 2)/SO(4, 1) × SO(6)/SO(5) constructed as a gauged WZW model and the non-Abelian T-dual of the AdS 5 × S 5 spacetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 89 publications
(164 reference statements)
6
134
0
Order By: Relevance
“…Indeed, the computation of the corresponding RG flow equations using gravitational methods was performed in [2,3] and is in agreement with results from field theoretical methods [8][9][10]. Furthermore, it was shown that these models, named generically as λ-deformed, can be embedded in specific cases of low dimensionality to supergravity [11][12][13][14][15], while their relation to η-deformations for group and coset spaces introduced in [16][17][18] and [19][20][21] respectively, via Poisson-Lie T-duality [22] and appropriate analytic continuations, was uncovered in [23][24][25][26][27]. More recently, the computation of the all-loop correlators for the…”
Section: Jhep03(2017)083supporting
confidence: 70%
See 1 more Smart Citation
“…Indeed, the computation of the corresponding RG flow equations using gravitational methods was performed in [2,3] and is in agreement with results from field theoretical methods [8][9][10]. Furthermore, it was shown that these models, named generically as λ-deformed, can be embedded in specific cases of low dimensionality to supergravity [11][12][13][14][15], while their relation to η-deformations for group and coset spaces introduced in [16][17][18] and [19][20][21] respectively, via Poisson-Lie T-duality [22] and appropriate analytic continuations, was uncovered in [23][24][25][26][27]. More recently, the computation of the all-loop correlators for the…”
Section: Jhep03(2017)083supporting
confidence: 70%
“…The example provided in section 4 seems to be resonably simple for that purpose. The analog works of embedding λ-deformations to supergravity in [11][12][13][14][15] should be very helpful in that direc-…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that there is a simple analytic continuation that takes the AdS 5 deformation to the S 5 deformation. Interestingly, just as for λ-deformations [77,78], it can be shown that the dilaton equation forces the same deformation parameter in AdS 5 and S 5 . Since η-deformations correspond to scaling limits of λ-deformations [79] this is not too surprising.…”
Section: η-Deformations and Mcybementioning
confidence: 91%
“…The η-deformation [10,11,41,42], which is an example of YB-deformations, is related to another integrable deformation called the λ-deformation [55,[97][98][99][100] via the PL T-duality [101,102]. This relation has been further generalized by intriguing works [103,104].…”
Section: Jhep12(2017)108mentioning
confidence: 99%